Biocompatibility of alumina‐based biomaterials–A review. Issue 4 (6th September 2018) - Rahmati, Maryam; Mozafari, Masoud
Abstract: In today's medicine world, alumina‐based biomaterials owing to their excellent biomechanical, and biocompatibility properties play a key role in biomedical engineering. However, the literature still suffers from not having a valid database regarding the protein adsorption and subsequently cell responses to these surfaces. Proteins by adsorption on biomaterials surfaces start interpreting the construction and also arranging the biomaterials surfaces into a biological language. Hence, the main concentration of this review is on the protein adsorption and subsequently cell responses to alumina's surface, which has a wide range biomedical applications, especially in dentistry and orthopedic applications. In the presented review article, the general principles of foreign body response mechanisms, and also the role of adsorbed proteins as key players in starting interactions between cells and alumina‐based biomaterials will be discussed in detail. In addition, the essential physicochemical, and mechanical properties of alumina surfaces which significantly impact on proteins and cells responses as well as the recent studies that have focused on the biocompatibility of alumina will be given. An in depth understanding of how the immune system interacts with the surface of alumina could prove the pivotal importance of the biocompatibility of alumina on its success in tissue engineering after implantation in body. Abstract : Alumina‐based biomaterials owing to their specific characteristics play a key role in biomedical engineering applications. This study reviews protein adsorption and subsequently cell responses to alumina surfaces. In addition, the essential physicochemical and mechanical properties of alumina surfaces, which significantly impact on proteins and cells responses are discussed.